Virtual communities of practice in the future of education - Enríquez, Silvia Cecilia (2019)
The authors of this chapter are founding members and part of the directing staff of Docentes en línea (Online teachers, Del), a virtual community of practice (VCoP) belonging to the Universidad Nacional de La Plata, Argentina (National University of La Plata, UNLP), which was created in 2012 and began its public activity in 2013. The term community of practice (CoP), coined by Lave and Wenger in 1991, has more recently been defined as “...groups of people who share a concern or a passion for something they do and learn how to do it better as they interact regularly” (Wenger-Trayner, 2015). They aim at making tacit knowledge explicit and can, like in our case, be a knowledge stewarding community (Dale, 2009).